The Long-Wave Depression, 1873-97 - Fels, Rendigs (The Review of Economics and Statistics, 1949)
ECONOMIC literature more often than not regards the period i873-97 in America as a long-wave depression. Such an interpretation rests on two facts. First, the trend of wholesale prices was downward during the period, and reversed itself immediately afterward.' Second, there was an unusually large number of depressed years compared to the periods before and after. For instance, Thorp labels I4 of the years from I873 to I897 inclusive as partly or wholly depression years and only 9 (2 unclassified) as partly or wholly prosperity, whereas for I898-I929 he lists 24 as prosperity and only 8 as depression.2 There has consequently been a tendency to regard I873-97 as comparable with the depressed years of the I930's and to explain both periods on the same grounds. Such comparisons create misleading impressions. The purpose of this note is to correct such impressions and to introduce into the discussion some factors ordinarily given insufficient attention.3